Guidance on selection of comparators for the risk assessment of genetically modified plants and derived food and feed - EFSA Panel on Genetically Modified Organisms (GMO) (EFSA Journal, 2011)
Abstract This opinion provides guidance in the area of comparators taking into account the requirements for the molecular characterisation, the food and feed and the environmental risk assessments. A key step in the risk assessment of genetically modified (GM) plants and derived food and feed is the identification of intended and unintended differences and equivalences between the GM plant and its comparator(s), taking into account the range of natural variation. In line with Regulation (EC) No 1829/2003 and Directive 2001/18/EC, the EFSA GMO Panel has, to date, required the use of non‐GM lines with comparable genetic background as comparators. In the case of vegetatively propagated crops, these are the isogenic lines. In the case of sexually propagated crops these are non‐GM lines as close as possible genetically to the GM plant under assessment. The identification and production of such comparators is becoming increasingly challenging due to the increasing complexity of GM plants, e.g. those developed by combining (stacking) events through conventional crosses, or those in which extensive compositional changes are targeted. Consequently, the EFSA GMO Panel has developed this guidance on the selection of comparators for the risk assessment of GM plants and derived food and feed. Whilst considering the requirements of Directive 2001/18/EC and Regulation (EC) No 1829/2003, the EFSA GMO Panel provides options which introduce flexibility in the selection of comparators based on sound scientific principles. This document addresses the selection of comparators for GM plants containing single or multiple events stacked by either conventional breeding, or by other approaches such as re‐transformation, co‐transformation and the use of multiple gene cassettes. The EFSA GMO Panel also considers situations where additional comparators may be required on a case‐by‐case basis and scenarios where appropriate comparators are not available (e.g. where extensive compositional changes are targeted). The EFSA GMO Panel recognises the different requirements for comparators for the molecular characterisation, food and feed and environmental components of the risk assessment.